Design Buck Converter for DC Motor of Transporter Model with IoT System - Salih, Mohamad Harith Haiqal; Utomo, Wahyu Mulyo (Evolution in Electrical and Electronic Engineering, 2023)
In this modern era with various types of technologies some of them need lower voltage to operate so the idea of a buck converter is very important with the efficiency being very high, at about 90%. This is why the buck converter is very important in industrial especially since this component is very related to DC motors. With the objective of designing the simulation, designing the buck converter and controlling it for DC motor applications using an IoT system. The design of the buck converter will focus on simulation in MATLAB Simulink with PCB design using Proteus. The system microcontroller uses ESP32 and has built-in Wi-Fi that very important for IoT systems. The DC motor power will use around 10W and estimated can carry around 2kg. Within the project process, there is a method to accomplish this project start with searching for any related research in the past few years to make it as a reference followed by the design of the circuit in a simulation then the design for hardware can start with designing the PCB, create the coding in microcontroller to create and lastly combined it with an installment of IoT system. There are a few key findings that can be observed from the data is as the different results when high duty cycle and low duty cycle, and the output voltage of the buck converter. In theory, the high-duty cycle of the buck converter will lower the voltage but it is more than 50% of the input voltage and with the low-duty cycle voltage will low less than 50% of the input voltage. Some suggestion for this project is to make sure to find an easy-to-use IC component for the PWM signal sent into the gate of MOSFET and add the feedback loop so it can control the PWM very clearly.